The versatile multi-functional substance NMN: its unique characteristics, metabolic properties, pharmacodynamic effects, clinical trials, and diverse applications - Yu, Bin; Jing, Xiaotong; Jia, Lina; Wang, Maoru; Liu, Liying; Ping, Songyuge; Wang, Yu; Yang, Min (Frontiers in Pharmacology, 2024)
β-nicotinamide mononucleotide (NMN) is a naturally occurring biologically active nucleotide widely present in organisms and an inherent substance in the human body. As a critical intermediate in synthesizing coenzyme I (NAD+), it widely participates in multiple biochemical reactions in the human body and is closely related to immunity, metabolism, and other factors. In recent years, NMN has rapidly developed and made significant progress in medicine, food, and healthcare. However, there is currently a lack of comprehensive reports on the research progress of NMN, as well as exploration and analysis of the current research achievements and progress of NMN. Therefore, this review is based on retrieving relevant research on NMN from multiple databases at home and abroad, with the retrieval time from database establishment to May 20, 2024. Subsequently, literature search, reading, key information extraction, organization, and summarization were conducted with the aim of providing a comprehensive and in-depth analysis of the characteristics, metabolic pathways, pharmacological effects, progress in human clinical trials, and wide applications of NMN in drug development and food applications. Furthermore, it offers personal insights into NMN's potential future developments and advancements to present the current development state and existing challenges comprehensively. Ultimately, this review aims to provide guidance and serve as a reference for the future application, innovation, and progression of NMN research.